What Is the Way Forward for IASB's Research Programme under the Evidence-Supported Approach? Some Analyses and Comments Based on the 2015 Agenda Consultation. (3rd May 2016) - Birt, Jacqueline; Hellman, Niclas; Jorissen, Ann; Mason, Stephani; Paananen, Mari
Abstract: The purpose of this paper is twofold: (1) the paper reviews the International Accounting Standards Board (IASB's) evidence-supported approach to standard setting, in particular the very broad definition of evidence that does not distinguish between scientific evidence used for developing the normative foundation (the standards) and observations in practice. Based on comparisons with medicine and auditing, we argue that there are good reasons for the IASB to separate scientific evidence from other sources of information. As producers of scientific evidence, the academic community must consider whether better alignment between publishing incentives and standard setting can be achieved. (2) Examining the 2015 Agenda Consultation, the 'top-five' research projects were identified: 'Disclosure Initiative – Principles of Disclosure', 'Primary Financial Statements', 'Financial Instruments with Characteristics of Equity', 'Business Combinations under Common Control', and 'Goodwill and Impairment'. In order to further support evidence-informed standard setting, we provide research-based comments on these projects (based on the European Accounting Association's Agenda Consultation comment letter).